Clinical implications of privilege awareness raising for couple and family therapists: a phenomenological qualitative design - Bridges, James Gavin (Kansas State University, 2020)
Over three decades have passed since Peggy McIntosh (1988) gave the invitation to unpack the invisible knapsack of privilege. Examples of this unpacking are usually identity specific (i.e, often focusing on race or gender), but have yet to address the process of privilege awareness broadly as it relates to any identity with social status. This study broadens the scope of privilege awareness to include any identity that holds power in society and addresses a gap in the literature on how this process influences the clinical work of couple and family therapists (CFTs). This study explores the privilege awareness experiences of CFTs and the influence of these experiences on their current clinical work. CFTs were asked to complete timelines of privilege awareness experiences and participate in a semi-structured interview. The following themes were common facilitators in the privilege awareness process among therapists: relationships with family and friends, proximity to diverse populations, the influence of oppression on their privilege awareness, and being in a CFT graduate program with faculty intending to increase social awareness through readings, assignments, and mentorship. CFTs identified common themes by which these experiences influenced their clinical work: self-of-the-therapist, socio-cultural attunement, and changes in policy and procedural changes.
Keywords: Privilege; Couple and family therapy; Qualitative; Phenomenology; Clinical training; Theory